Analysis of the Maranhão Verde Project ‘‘Protective Forest of Watersheds’’ in São Luís – MA (REMUNOM, 2024)
This monograph brings reflections about the analysis of the Maranhão Verde Project, especially about the importance of conservation and recovery of natural resources. The objective of the research is to analyze the results of the Program in São Luís-MA. In view of this, the need to protect conservation units (CU) is clear. and recovery of native vegetation around the Bacanga State Park, in addition, the criteria for selecting families in the program, guidelines and typologies of the National System of Nature Conservation Units (SNUC) are discussed, emphasizes the importance of the MA Verde program from an agroecological perspective. It is worth highlighting the final number of 262 families, subdivided into 6 groups and, benefiting bimonthly with the amount of R$300.00 for the production and planting of seedlings of various species throughout the year 2019 to 2021. The Maranhão Verde Project (PMV), had international recognition by the Latin America Green award, it was among the 500 best programs in Latin America Green 2021. The importance of the project is highlighted, which above all aims at the conscious and sustainable use of such resources in order to preserve and guarantee such resources for this and future generations, minimizing environmental impacts while conserving biodiversity.